2019
DOI: 10.37190/abb-01429-2019-02
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to reduce loads of the locomotor system during the landing phase of dance figures? Biomechanical analysis of the landing phase in Grand Jeté, Entrelacé and Ballonné

Abstract: The objective of the work was to determine biomechanical parameters influencing loads affecting the musculoskeletal system and shock absorption during the landing phase in Grand Jeté, Entrelacé and Ballonné. Methods: Motion kinematics measurements of the landing phase in GrandJeté, Entrelacé and Ballonné were carried out using the optical APAS system, and measurements of the GRF components-using Kistler platform. The research was carried out for three professional dancers. Kinematic and kinetic parameters of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Interestingly, previous studies have shown that an intense training program begun at the age of 10 leads to specific structure and appearance of the dancer's musculoskeletal system [33][34][35][36]. First of all, due to repeated impact forces the increased bone mineralization is observed in the body parts which are regularly loaded [33,35,37]. Secondly, due to specific, more or less forced, mechanisms employed to achieve TO, different muscular strategies are developed in classical positions, as presented in present study.…”
Section: Plos Onementioning
confidence: 56%
“…Interestingly, previous studies have shown that an intense training program begun at the age of 10 leads to specific structure and appearance of the dancer's musculoskeletal system [33][34][35][36]. First of all, due to repeated impact forces the increased bone mineralization is observed in the body parts which are regularly loaded [33,35,37]. Secondly, due to specific, more or less forced, mechanisms employed to achieve TO, different muscular strategies are developed in classical positions, as presented in present study.…”
Section: Plos Onementioning
confidence: 56%
“…Considering comprehensive scientific analyses of the technical performance of various dance styles, such as the classics [13][14][15], modern dance [16][17][18], Irish dance [19] and a whole range of folk dances from various regions of the world [20], there is a lack of a detailed technical analysis of flamenco dance in the scientific literature [12].…”
Section: Introductionmentioning
confidence: 99%
“…Shock waves generated during dancing are propagated along the human musculoskeletal system, becoming one of the main reasons for joint degeneration ( Gorwa et al, 2019b ). When dancers strike the ground, they subject structures of the supporting limb (joints, muscles, tendons, ligaments) to serious loads due to high peaks of force which are several times their body weight ( Echegoyen et al, 2013 ; Gorwa et al, 2019b ). A key component in reducing vertical ground reaction force (GRF) is damping and this is performed with the legs.…”
Section: Introductionmentioning
confidence: 99%
“…A key component in reducing vertical ground reaction force (GRF) is damping and this is performed with the legs. The knee appears to be the main modulator of leg stiffness, as the lever arm lengths of the femur and tibia place the knee in the best position of all the lower extremity joints to help attenuate the vertical GRF ( Gorwa et al, 2019a , 2019b ). There are several studies researching the level of GRF in percussive dances ( Echegoyen et al, 2013 ; Klopp, 2017 ; Mayers et al, 2010 ), but only one study has focused on GRF in the flamenco dance ( Echegoyen et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%